2013
DOI: 10.1007/s12105-013-0468-6
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Gland Lymphoproliferative Disorders: A Canadian Tertiary Center Experience

Abstract: Salivary gland lymphoproliferative disorders (SGLD) are very rare tumors and clinicopathological data is sparse. In a Canadian series of 30 cases, extracted from the surgical pathology files of The Ottawa Hospital between 1990 and 2010, a clinical, histopathological, and immunophenotypic analysis was conducted. Tumors were staged using the Ann Arbor staging and classified using the World Health Organization 2008 classification. There were 15 salivary gland (SG) primary lymphomas with localized disease, predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Although no residual MALT lymphoma component was present in this case, the possibility of a high-grade transformation of thymic MALT lymphoma has been reported previously [ 8 ]. Primary salivary gland high-grade B-cell lymphomas occurring with or without a preceding MALT lymphoma have also been observed in Sjögren syndrome [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although no residual MALT lymphoma component was present in this case, the possibility of a high-grade transformation of thymic MALT lymphoma has been reported previously [ 8 ]. Primary salivary gland high-grade B-cell lymphomas occurring with or without a preceding MALT lymphoma have also been observed in Sjögren syndrome [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that MALT lymphomas are the most common type among primary SGLs, 8-13 but some studies have shown that FL is as common as MALT lymphoma in the salivary gland. 14,15 Paliga et al reported that out of 15 primary SGL cases, 5 were FLs (33%) and 6 were MALT lymphomas (40%). 15 In Japan, Kojima et al and Nakamura et al indicated the relatively high frequency of FL, being 30% 19 and 22%, 9 respectively, among SGL.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Paliga et al reported that out of 15 primary SGL cases, 5 were FLs (33%) and 6 were MALT lymphomas (40%). 15 In Japan, Kojima et al and Nakamura et al indicated the relatively high frequency of FL, being 30% 19 and 22%, 9 respectively, among SGL. In our study, FL was also as common as MALT lymphoma among primary SGLs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hodgkin lymphoma presenting as a primary parotid mass is rare, representing only 3.5% to 6% of primary parotid gland lymphomas and 0.3% of all Hodgkin lymphoma cases in general. 10,11,13 To date, <10 cases have been reported in the literature. 14,15 We are aware of only a single-case report of NLPHL involving the parotid gland.…”
Section: Discussionmentioning
confidence: 99%